2020
DOI: 10.3389/fimmu.2020.581517
|View full text |Cite|
|
Sign up to set email alerts
|

Brucella-Induced Downregulation of lncRNA Gm28309 Triggers Macrophages Inflammatory Response Through the miR-3068-5p/NF-κB Pathway

Abstract: ObjectivesThe underlying mechanism of the inflammatory response against Brucellosis caused by Brucella remains poorly understood. This study aimed to determine the role of long non-coding RNAs (lncRNAs) in regulating of inflammatory and anti-Brucella responses.Materials and methodsMicroarray analysis was performed to detect differentially expressed lncRNAs in THP-1 cells infected with an S2308 Brucella strain. The candidate lncRNAs were screened using bioinformatic analysis and siRNAs; bioinformatic prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…To verify the role of lncRNA PKN2-AS1 and AC068888.1 in the assessment of disease severity and in ammation, our clinical study found that those two lncRNAs were signi cantly correlated with SOFA, APACHE II scores and Lac level, but weakly correlated with PCT and CRP levels. The possible explanation is that, like other lncRNAs (such as MALAT1 and NEAT1), these two lncRNAs may promote the production of in ammatory factors through the NF-κB or TLRs pathway [42,43], aggravating the in ammation and organ dysfunction. In the diagnosis of sepsis, lncRNA PKN2-AS1 (AUC = 0.704) and AC068888.1 (AUC = 0.812) clearly distinguished patients with septic shock from those without septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…To verify the role of lncRNA PKN2-AS1 and AC068888.1 in the assessment of disease severity and in ammation, our clinical study found that those two lncRNAs were signi cantly correlated with SOFA, APACHE II scores and Lac level, but weakly correlated with PCT and CRP levels. The possible explanation is that, like other lncRNAs (such as MALAT1 and NEAT1), these two lncRNAs may promote the production of in ammatory factors through the NF-κB or TLRs pathway [42,43], aggravating the in ammation and organ dysfunction. In the diagnosis of sepsis, lncRNA PKN2-AS1 (AUC = 0.704) and AC068888.1 (AUC = 0.812) clearly distinguished patients with septic shock from those without septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…miR-139-5p has been implicated in maintaining intestinal homeostasis and protection against colitis in vivo [ 30 ]. Inhibition of miR-3068-5p represses p65 phosphorylation and reduces NLRP3 inflammasome and IL-1 β and IL-18 secretion [ 10 ]. These findings indicate that dysregulated circRNAs may interact with these miRNAs, thus promoting NEC development.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies report that circRNAs are expressed in most human cells and serve a critical role in regulating gene expression at the posttranscriptional level [ 6 ]. circRNAs have been linked to certain diseases, such as diabetic colonic dysmotility [ 7 ], inflammatory bowel disease [ 8 ], sepsis [ 9 ], innate colitis [ 10 ], and colorectal cancer [ 11 ]. For instance, circHIPK3 was proved to be a major regulator of intestinal epithelial repair following acute injury [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the plasmid was directly mixed with transfection regent (1 : 1) and mixed by using a pipette (10–15 times). Following incubation at room temperature for 15 min, the mixture was added to the cell culture plates, mixed gently, and incubated in a CO 2 incubator for 24 h [ 17 ].…”
Section: Methodsmentioning
confidence: 99%